Republic of Belarus : Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This Statistical Appendix for 2001-05 for the Republic of Belarus highlights the GDP; capital investment by sector; industrial production; inventories; production and consumption of energy; administered prices of household services; tariffs and cost coverage of utility prices for households; average monthly wages; price and wage developments; money income and expenditures of the population; labor market indicators; average monthly employment by sector; profits and losses of enterprises; energy debts of enterprises; tax arrears; government debt; export and import statistics; and other selected statistical data.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet